Sustainable Livelihoods-Based Assessment of Adaptive Capacity to Climate Change The Case of organic and conventional vegetable farmers in La Trinidad, Benguet, Philippines - Colting-Pulumbarit, Clarice; Lasco, Rodel D.; Rebancos, Carmelita M.; Coladilla, Jesusita O. (2018)
Climate change adaptation is vital for farmers in developing countries due to the high vulnerability of agricultural livelihoods. Scientific literature proposed that organic farming is a promising adaptation strategy, but micro-level studies are lacking. This study compared the adaptive capacity to climate risks of organic and conventional vegetable farmers in La Trinidad, Benguet in the Philippines. Guided by the Sustainable Livelihoods framework, thirty variables under the five livelihood capitals were used to compute Household Adaptive Capacity Index (HACI). Organic farming households have higher adaptive capacity than the conventional group, and have higher natural, financial, human, and social capital. The higher adaptive capacity of organic farmers was due to farm practices related to organic agriculture such as crop diversification, sustainable land management, and participation in organizations. This indicated that organic farming potentially enhances adaptive capacity of vegetable farming households. Findings support literature on the contribution of organic farming to the resilience of agricultural systems. Increased support toward higher adoption of organic farming in areas with similar context is recommended for adaptive management to climate change.
Keywords: Charter change; Organic farming; Agriculture